European Union development assistance to Thailand - Rusiecka, Kamila (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
Thailand has been significantly developing its economy for several decades and aims to become a leader in Southeast Asia. The European Union plays a significant role in this regard. The aim of this chapter is to illustrate EU development assistance to Thailand, which will enable addressing questions regarding Thai authorities' ambitions, the nature of EU assistance, and its significance for Thailand's development. The chapter will present the EU's policy towards the Southeast Asia region, EU-Thailand relations, and, most importantly, various EU development assistance projects for Thailand will be presented and analyzed, ranging from education and sustainable development to humanitarian issues and human rights.